1997
DOI: 10.1161/01.cir.96.3.864
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Enalapril and Verapamil on Myocardial Blood Flow in Systemic Hypertension

Abstract: In arterial hypertension, MBF during pacing tachycardia and after dipyridamole is impaired. Successful therapy with verapamil increases MBF response to these stimuli, independent of changes in perfusion pressure and left ventricular mass. These results suggest that verapamil directly improves coronary microcirculatory function in hypertension. Enalapril does not significantly change MBF but reduces the inhomogeneity of regional flow distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 62 publications
1
37
0
2
Order By: Relevance
“…Others found weak and clinically not relevant relationship between LV mass index and CFR. 15,17 Motz et al 46 first reported coronary endothelial dysfunction in hypertensive undergoing coronary angiography for angina pectoris. In our study, FMD findings did not impact on the lack of relation between LV mass index and CFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others found weak and clinically not relevant relationship between LV mass index and CFR. 15,17 Motz et al 46 first reported coronary endothelial dysfunction in hypertensive undergoing coronary angiography for angina pectoris. In our study, FMD findings did not impact on the lack of relation between LV mass index and CFR.…”
Section: Discussionmentioning
confidence: 99%
“…With this regard, early experimental and clinical invasive studies reported association of LVH with reduced CFR. [6][7][8][9][10] However, others failed to find significant independent relationship between CFR and LVH, [11][12][13][14][15][16][17] and the independent relation between LVH and abnormal CFR remains disputed. In addition, LVH is independently associated with coronary artery disease, 18 which may confound the relation between LVH and CFR.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,[17][18][19][20] Two of these used the PET technique, 2,4 whereas 4 studies used the argon gas chromatography technique. [17][18][19][20] However, using the latter invasive procedure only allows investigation of hypertensive patients with symptoms of ischemia, whereas the PET technique permits investigations of asymptomatic patients, who constitute the majority of the hypertensive population.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] This abnormality could result in reduced exercise capacity and myocardial ischemia in situations with high oxygen demands, 1,5 but the background for this microcirculatory disturbance is not clear. The presence of left ventricular hypertrophy may contribute, 6,7 but structural remodeling of myocardial resistance arteries also seems important.…”
mentioning
confidence: 99%
See 1 more Smart Citation